Cigarette smoke alters circRNA expression in human T-cells [version 2; peer review: 1 approved, 2 approved with reservations] - Kenneth W. Witwer; Ashley E. Russell; So Jin Hong; Zhaohao Liao (F1000Research)
Circular RNAs (circRNAs), once thought to be a result of splicing errors, have been found to be involved in various molecular processes and the pathology of various diseases, including cancer and neurodegenerative diseases. Additionally, circRNA expression was found to be altered by lifestyle habits, such as smoking cigarettes. Past studies have revealed that the rate of smoking remains high in people living with human immunodeficiency virus (HIV). In this study, we isolated total RNA from uninfected T-cells that have been exposed to cigarette smoke and compared the expression levels of circRNAs to those of T-cells that were not exposed to cigarette smoke. We identified certain circRNAs that were upregulated or downregulated in T-cells when exposed to cigarette smoke. These data indicate that the study of circRNAs is warranted within the context of HIV.